Empowering tribal households through water security and livelihood transformation - H. R., Chikkathimme Gowda; T., Amrutha; Singh, N. Uttam; Pual, Pampi; Biam, Kamni P.; Yumnam, A.; Mishra, V. K.; Singh, B. P. (Indian Farming, 2025)
Jalkund is a water harvesting technology specifically designed and developed for hilltop farm households to meet critical water needs. Farmers utilized the stored water to irrigate small vegetable plots, cultivating crops such as cabbage, cauliflower, and broccoli, which provided substantial income. In addition to crop cultivation, the stored water supported poultry and piggery activities, helping farmers generate supplementary income. The water was also used for fish rearing, further enhancing their livelihood opportunities. The technology proved economically viable, with all farm activities contributing significantly to household income. Overall, adopting the Jalkund improved farm income, particularly during water-scarce periods. This water harvesting technology was crucial in providing water security and sustaining farm households through diversified agricultural and allied activities.